Study of the Effect of Sodium Dodecyl Sulfate (SDS) and Acridine Orange on the Isolation of Plasmid and Antimicrobial Resistance Pattern of Clinical Isolates of Klebsiella Sp (Daffodil International University Journal of Science and Technology, 2012)
For a six months period a total of 25 Klebisiella sp. samples collected from different diagnostic centers were tested for their antimicrobial susceptibility pattern against 16 antimicrobials. All isolates under study showed resistance against cephalexin, cephradine, ciporfloxacin, cloxacillin, erythromycin, oxacillin, rifampicin and tetracycline. Most of the isolates were resistant to amoxicillin (92%), vancomycin (96%), neomycin (84%) and chloramphenicol (76%). Least number of isolates showed resistance to tetracycline (36%), ceftriaxone (40%) and gentamycin (56%), respectively. Out of the 25 isolates, 7 multidrug resistant isolates were selected and they were grown in varying concentrations of Sodium Dodecyl Sulfate (SDS) in Luria broth and their plasmid profile was analysed. Distinct bands of plasmid were observed when the multidrug resistant strains of Klebsiella sp. were grown in 5% SDS and acridine orange (10μg/ml) in Luria broth. On being treated with 5% SDS and 5% SDS along with acridine orange, one isolate (isolate no. 3) developed sensitivity against ceftriaxone, ciprofloxacin, co-trimoxazole, gentamycin and neomycin. Keywords: Klebsiella sp.; plasmid; antimicrobial susceptibility; multidrug resistance; sodium dodecyl sulfate (SDS)   DOI: http://dx.doi.org/10.3329/diujst.v7i1.9646   Daffodil International University Journal of Science and Technology Vol.7(1) 2012 38-43